Cu-Al-Ca bifunctional material with core-shell structure as well as preparation method and application of Cu-Al-Ca bifunctional material

By using Cu-Al-Ca bifunctional material with a core-shell structure, using adsorbents composed of Al2O3 and CaO and a catalyst composed of metal Cu, the problem of low CO2 capture capability decay and conversion rate in the cyclic ICCU-RWGS reaction in the prior art is solved, and efficient CO2 capture and stable high CO2 conversion rate is achieved, reducing the energy consumption and cost of CCUS technology.

CN119701864APending Publication Date: 2025-03-28CHINA DATANG GRP TECH INNOVATION CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510054553.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the cyclic ICCU-RWGS reaction, the CO2 capture capacity has severely decayed, the CO2 conversion rate is low, the CO product selectivity is poor, and the preparation process has large energy consumption and poor performance.

Method used

A Cu-Al-Ca bifunctional material with a core-shell structure is used, and its core is an Al-Ca adsorbent composed of Al2O3 and CaO, and the shell is metal Cu. The metal Cu is uniformly loaded on the surface of the Al-Ca adsorbent particles by magnetron sputtering method to regulate the kinetics of the counterwater gas transformation reaction of the carbonate decomposition product CO2.

Benefits of technology

It achieves efficient CO2 capture, stable high CO2 conversion rate and excellent CO product selectivity, high cycle stability, and reduces the energy consumption and cost of CCUS technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701864A_ABST
    Figure CN119701864A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-Al-Ca bifunctional material with a core-shell structure as well as a preparation method and application of the Cu-Al-Ca bifunctional material. A core of the Cu-Al-Ca bifunctional material is an Al-Ca adsorbent composed of Al2O3 and CaO, and a shell of the Cu-Al-Ca bifunctional material is metal Cu; wherein based on the total mass of the Cu-Al-Ca bifunctional material, the mass fraction of the metal Cu in the bifunctional material is 0.5-3.0 wt%, and based on the total mole number of the metal elements of the Cu-Al-Ca bifunctional material, the mole ratio of the Al element to all the metal elements is 1-10%. The Cu-Al-Ca bifunctional material has a stable structure, is not easy to sinter and inactivate, can be used for CO2 capture and in-situ reverse water gas shift preparation of CO, still has excellent CO2 absorption capacity, CO2 conversion rate and CO product selectivity after multiple times of cyclic utilization, and has high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Cu-Al-Ca dual-functional material with a core-shell structure and a preparation method and application thereof, belonging to the technical field of carbon dioxide capture, utilization and storage (CCUS). Background Art

[0002] Since the Industrial Revolution, excessive CO2 emissions from industrial activities have been the main cause of the greenhouse effect. The resulting global climate disasters, such as extreme high temperatures, droughts, and ocean acidification, have seriously affected the survival of life on Earth.

[0003] The extensive use of fossil energy is the root cause of large-scale CO2 emissions and the greenhouse effect, but humans are still heavily dependent on fossil energy at this stage and will continue to emit CO2. Therefore, controlling CO2 emissions has become an urgent problem to be solved in my country's energy and other related industries. Carbon dioxide capture, utilization and storage (CCUS) is one of the most promising large-scale carbon emission reduction technology routes, which mainly consists of four parts: i) carbon dioxide capture, ii) carbon dioxide compression, storage and transportation, iii) carbon dioxide utilization, and iv) carbon dioxide storage. This technology captures CO2 from flue gas from thermal power plants, metallurgical waste gas, and cement kiln exhaust gas through adsorbents, and then transports it to chemical plants for utilization through compression, liquefaction, pipeline storage and transportation, or transports it to geological landfills such as abandoned oil fields for geological storage.

[0004] At present, all parts of CCUS are in a discrete stage. The huge energy consumption of CO2 capture, CO2 compression, storage and transportation, and CO2 utilization restrict the industrial operation of CCUS technology. In response to the energy consumption problem of CCUS technology, some scholars have recently proposed an integrated flue gas CO2 capture and in-situ reverse water gas shift technology (ICCU-RWGS), which captures CO2 in flue gas (~15vol.%) through the adsorbent in the bifunctional material (the adsorbent component is converted into carbonate); and then in renewable green hydrogen, the carbonate is converted in situ into high-value CO (chemical basic raw material) through the catalyst component in the bifunctional material, and the carbonate is regenerated into fresh absorbent material. The bifunctional material can efficiently capture CO2 in multiple cycle reactions and convert it into high-value products in situ.

[0005] The technical advantage of ICCU lies in the in-situ integration of CO2 capture and CO2 utilization, which can avoid the CO2 compression liquefaction and CO2 storage and transportation links between CO2 capture and CO2 utilization from the source, greatly reducing the technical energy consumption and cost of CCUS. The technical core of ICCU lies in the design and development of bifunctional materials. The CO2 capture capacity of the adsorbent component in the bifunctional material will decay as the reaction proceeds during multiple cycles, and the catalyst component will also undergo certain sintering and particle aggregation during multiple cycles. In particular, the catalyst component often interacts with the adsorbent, thereby depleting the number of active sites of the adsorbent.

[0006] CO is a basic raw material for chemical processes and has great application potential in the chemical industry. In recent years, the capture of CO2 in flue gas and its in-situ conversion into CO has been proven to have good application prospects.

[0007] At present, the CO2 capture capacity of existing bifunctional materials is seriously attenuated during the cyclic ICCU-RWGS reaction process. Secondly, during the carbonate decomposition process, the rapid release of CO2 reduces its conversion rate, resulting in the escape of CO2 and the decline of product gas quality. At the same time, the preparation process of bifunctional materials still consumes a lot of energy and the performance is not ideal. It is imperative to develop more efficient bifunctional materials to achieve high CO2 capture efficiency, CO2 catalytic conversion rate, and CO product selectivity in the ICCU-RWGS process. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] In view of the above defects or improvement needs in the prior art, the present invention provides a Cu-Al-Ca bifunctional material with a core-shell structure and a preparation method and use thereof. The Cu-Al-Ca bifunctional material of the present invention has high CO2 capture efficiency, CO2 catalytic conversion rate, good CO product selectivity, and excellent cycle stability.

[0010] Solutions for solving problems

[0011] [1] A Cu-Al-Ca bifunctional material with a core-shell structure, wherein the core of the bifunctional material is an Al-Ca adsorbent composed of Al2O3 and CaO, and the shell is metal Cu;

[0012] Wherein, based on the total mass of the Cu-Al-Ca dual-functional material, the mass fraction of metal Cu in the dual-functional material is 0.5-3.0wt%,

[0013] Wherein, based on the total molar number of metal elements in the Cu-Al-Ca dual-functional material, the molar ratio of Al element to all metal elements is 1-10%.

[0014] [2] A method for preparing the Cu-Al-Ca dual-functional material according to [1], comprising the following steps:

[0015] S1: dissolving a Ca precursor and an Al precursor to obtain a metal ion solution;

[0016] S2: dissolving citric acid in the metal ion solution to obtain a mixed solution;

[0017] S3: stirring and heating the mixed solution to form a wet gel;

[0018] S4: drying and aging the wet gel to form a dry gel;

[0019] S5: calcining the dry gel to obtain Al-Ca adsorbent powder;

[0020] S6: granulating the Al-Ca adsorbent powder to obtain Al-Ca adsorbent particles;

[0021] S7: Spraying metal Cu on the Al-Ca adsorbent particles on a vibration table by magnetron sputtering to obtain the Cu-Al-Ca dual-functional material.

[0022] [3] The preparation method according to [2], in step S1,

[0023] The Ca precursor is calcium nitrate, the Al precursor is aluminum nitrate, the solvent used for dissolution is water, and the molar ratio of nitrate ions in the calcium nitrate and aluminum nitrate to water is 1:30 to 1:50.

[0024] [4] The preparation method according to [2] or [3], wherein in step S2,

[0025] The molar ratio of the metal ions to the citric acid in the metal ion solution is 1:1 to 1:1.5.

[0026] [5] The method according to [2] or [3], wherein in step S3,

[0027] The stirring speed is 200-300 rpm, the heating is oil bath heating, and the temperature of the oil bath heating is 80-90°C.

[0028] [6] The preparation method according to [2] or [3],

[0029] In step S4, the drying and aging temperature is 110-140°C;

[0030] In step S5, the calcination temperature is 750-900°C, and the calcination time is 1.5-4 hours.

[0031] [7] The method according to [2] or [3], wherein in step S6,

[0032] The granulation is performed using a hydraulic granulator, wherein the processing pressure is 10 MPa;

[0033] The particle size of the Al-Ca adsorbent particles obtained after granulation is 40-60 meshes.

[0034] [8] The method according to [2] or [3], wherein in step S7,

[0035] In the magnetron sputtering, the Al-Ca adsorbent particles are placed on a vibration table, and the vibration frequency of the vibration table is 20-50 rpm; the spraying power of the magnetron sputtering is 200-250 W; and the spraying time of the magnetron sputtering is 30-120 min.

[0036] [9] A use of the Cu-Al-Ca bifunctional material described in [1] for CO2 capture and in-situ reverse water gas shift production of CO.

[0037] Effects of the Invention

[0038] The Cu-Al-Ca bifunctional material with a core-shell structure of the present invention has a porous structure and a high specific surface area, which is conducive to CO2 adsorption and can promote the diffusion of reactants and products. It has a stable structure and is not easy to be sintered and deactivated. After multiple cycles, it still has excellent CO2 absorption capacity, CO2 conversion rate and CO product selectivity, and has high cycle stability. By uniformly loading the metal Cu shell on the surface of the Al-Ca adsorbent particles by magnetron sputtering, the reverse water gas shift reaction kinetics of the carbonate decomposition product CO2 can be effectively regulated, CO2 capture and in-situ reverse water gas shift preparation of CO are achieved, and the cost generated in the CO2 storage and transportation process is eliminated, which greatly reduces the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the preparation process of Al-Ca adsorbent particles in Example 1.

[0040] Figure 2 Schematic diagram of the magnetron sputtering process of the method for preparing the Cu-Al-Ca dual-functional material of Example 1.

[0041] Figure 3 Schematic diagram of the process of CO2 capture and in-situ reverse water gas shift production of CO using the Cu-Al-Ca bifunctional material of Example 1.

[0042] Figure 4 Performance comparison chart of cyclic CO2 capture and in-situ reverse water gas reaction of Example 1-3 and Comparative Example 1-2.

[0043] Figure 5 SEM / EDX-Mapping spectrum of the Cu-Al-Ca dual-functional material of Example 1. DETAILED DESCRIPTION

[0044] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0045] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0046] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0047] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0048] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0049] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.

[0050] The present invention provides a Cu-Al-Ca bifunctional material with a core-shell structure, characterized in that the core of the bifunctional material is an Al-Ca adsorbent composed of Al2O3 and CaO, and the shell is metal Cu;

[0051] Wherein, based on the total mass of the Cu-Al-Ca dual-functional material, the mass fraction of metal Cu in the dual-functional material is 0.5-3.0wt%,

[0052] Wherein, based on the total molar number of metal elements in the Cu-Al-Ca dual-functional material, the molar ratio of Al element to all metal elements is 1-10%.

[0053] In the Cu-Al-Ca bifunctional material of the present invention, metal Cu is the active catalytic component of the in-situ reverse water gas shift of CO2, which not only provides sufficient catalytic active sites, but also, due to the spatially confined structure, enables the CO2 product of carbonate decomposition to be effectively converted in a timely manner, thereby avoiding the escape of CO2 caused by the rapid decomposition of carbonates, which in turn affects the quality of the product gas.

[0054] In the Cu-Al-Ca bifunctional material of the present invention, based on the total mass of the Cu-Al-Ca bifunctional material, the mass fraction of metal Cu in the bifunctional material is 0.5-3.0wt%, for example, it can be 0.81wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.7wt%, 1.8wt%, 2.0wt%, 2.5wt%, 2.7wt%, etc.

[0055] In the Cu-Al-Ca bifunctional material of the present invention, the core of the bifunctional material is an Al-Ca adsorbent composed of Al2O3 and CaO. Among them, CaO is used to capture CO2 in flue gas; while Al2O3 itself has no CO2 capture ability and no catalytic activity, but Al2O3 reacts with CaO to generate Ca3Al2O6 inert oxide, which is used as an inert support. When it is uniformly dispersed in the bifunctional material, it can effectively inhibit the sintering and deactivation of the bifunctional material.

[0056] Based on the total molar number of metal elements in the Cu-Al-Ca bifunctional material, the molar ratio of Al element to all metal elements is 1-10%. The content of Al2O3 is a critical control parameter. When Al2O3 is too much, the number of CO2 adsorption sites per unit mass in the bifunctional material will be reduced, affecting the CO2 capture capacity and increasing the reaction energy consumption. Therefore, based on the total molar number of metal elements in the Cu-Al-Ca bifunctional material, the molar ratio of Al element to all metal elements is 1-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc.

[0057] The present invention also provides a method for preparing the Cu-Al-Ca dual-functional material according to the present invention, which comprises the following steps:

[0058] S1: dissolving a Ca precursor and an Al precursor to obtain a metal ion solution;

[0059] S2: dissolving citric acid in the metal ion solution to obtain a mixed solution;

[0060] S3: stirring and heating the mixed solution to form a wet gel;

[0061] S4: drying and aging the wet gel to form a dry gel;

[0062] S5: calcining the dry gel to obtain Al-Ca adsorbent powder;

[0063] S6: granulating the Al-Ca adsorbent powder to obtain Al-Ca adsorbent particles;

[0064] S7: Spraying metal Cu on the Al-Ca adsorbent particles on a vibration table by magnetron sputtering to obtain the Cu-Al-Ca dual-functional material.

[0065] According to the preparation method of the present invention, in step S1, the Ca precursor is calcium nitrate, the Al precursor is aluminum nitrate, the solvent used for dissolution is water, and the molar ratio of nitrate ions in the calcium nitrate and aluminum nitrate to water is 1:30 to 1:50, for example, 1:35, 1:40, 1:45, etc.

[0066] According to the preparation method of the present invention, in step S2, the molar ratio of metal ions to citric acid in the metal ion solution is 1:1 to 1:1.5, for example, 1:1.1, 1:1.2, 1:1.3, 1:1.4, etc.

[0067] According to the preparation method of the present invention, in step S3, the stirring speed is 200-300 rpm, the heating is oil bath heating, and the temperature of the oil bath heating is 80-90°C, preferably 85°C.

[0068] According to the preparation method of the present invention, in step S4, the wet gel is aged in an oven at a temperature of 110-140°C, such as 115°C, 120°C, 125°C, 130°C, 135°C, etc., preferably 120°C.

[0069] According to the preparation method of the present invention, in step S5, the dry gel is calcined in a muffle furnace at a rapid temperature increase. The calcination temperature is 750-900°C, for example, 800°C, 820°C, 840°C, 850°C, 860°C, 880°C, etc., preferably 850°C. The heating temperature for heat treatment in the muffle furnace is 80°C / min. The calcination time is 1.5-4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, etc., preferably 2 hours.

[0070] According to the preparation method of the present invention, in step S6, a hydraulic granulator is used for granulation, wherein the processing pressure is 10 MPa; the particle size of the Al-Ca adsorbent particles obtained after granulation is 40-60 meshes.

[0071] According to the preparation method of the present invention, in step S7, in the magnetron sputtering, the Al-Ca adsorbent particles are placed on a vibration table, and the vibration frequency of the vibration table is 20-50 rpm; the spraying power of the magnetron sputtering is 200-250 W; and the spraying time of the magnetron sputtering is 30-120 min.

[0072] The present invention also provides a use of the Cu-Al-Ca dual-functional material according to the present invention for CO2 capture and in-situ reverse water gas shift to prepare CO.

[0073] The steps of using the Cu-Al-Ca dual-functional material of the present invention for CO2 capture and in-situ reverse water gas shift to produce CO are as follows:

[0074] Step 1: placing the Cu-Al-Ca dual-functional material of the present invention into a fixed bed reactor;

[0075] Step 2: Heat up the fixed bed reactor, introduce flue gas with a CO2 concentration of 13%-17% into the reactor to capture CO2, and stop the ventilation after the capture is completed;

[0076] Step 3: Maintaining the temperature of the fixed bed reactor in step 2, introducing H2 into the fixed bed reactor to cause a reverse water gas reaction.

[0077] In the present invention, in step 2, CO2 is captured by CaO in the Cu-Al-Ca dual-functional material, and the adsorbent component is converted into carbonate. The time for passing CO2 is 20-60 minutes, preferably 30 minutes.

[0078] In the present invention, in step 2, the temperature of the fixed bed reactor is set to 500-800°C, preferably 650°C. CO2 capture and in-situ reverse water gas reaction are preferably completed under isothermal conditions, which can greatly reduce the energy consumption of the process; when the temperature is lower than 650°C, the CO2 capture kinetics is slow, and the CO2 in the flue gas cannot be well captured. At the same time, the carbonate decomposition rate is slower, which easily causes the CO2 capture and carbonate hydrogenation reaction to be mismatched; when the temperature is higher than 650°C, the carbonate hydrogenation conversion rate is too fast, which easily leads to CO2 escape (the CO2 product does not have time to react with H2 to undergo reverse water gas shift and be converted into CO).

[0079] In the present invention, in step three, renewable green hydrogen converts carbonate into high-value CO in situ under the action of metal Cu in the bifunctional material, and regenerates the carbonate into a fresh absorbent.

[0080] In the present invention, in step three, the concentration of H2 is 10%-100%, and the time for introducing H2 is 20-60 minutes, or no more CO is generated.

[0081] Example

[0082] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0083] Example 1

[0084] Cu-Al-Ca dual-functional material: Cu-Al10-Ca90 (molar ratio)

[0085] S1: adding calcium nitrate tetrahydrate and aluminum nitrate nonahydrate into deionized water in the above molar ratio, stirring to completely dissolve them, to obtain a metal ion solution;

[0086] S2: adding citric acid in an amount 1 times the molar amount of the metal cation to the metal ion solution, stirring to completely dissolve the citric acid, and obtaining a mixed solution;

[0087] S3: placing the mixed solution in an oil bath and stirring and heating until a uniform wet gel is formed; wherein the stirring speed is 300 rpm and the oil bath heating temperature is 85° C.;

[0088] S4: placing the wet gel in an oven for drying and aging until a dry gel is formed; wherein the drying and aging temperature is 120° C.;

[0089] S5: placing the dry gel in a muffle furnace and rapidly heating it up in an air atmosphere to obtain a fluffy Al-Ca adsorbent powder; wherein the heating rate of the muffle furnace heat treatment is 80° C. / min, the calcination temperature is 850° C., and the calcination time is 2 hours;

[0090] S6: collecting the fluffy Al-Ca adsorbent powder and granulating it in a hydraulic granulator to screen out 40-60 mesh Al-Ca adsorbent particles; wherein the processing pressure on the hydraulic granulator is 10 MPa;

[0091] S7: placing the Al-Ca adsorbent particles in a Figure 2 In the homemade magnetron sputtering sample stage shown, the sample is continuously vibrated by a vibration table, and the catalytic metal Cu in the plasma state will be deposited on the surface of the Al-Ca adsorbent particles to form a Cu-Al-Ca dual-functional material with a core-shell structure;

[0092] Among them, the vibration frequency of the vibration table in magnetron sputtering is 30rpm; the spraying power of magnetron sputtering is 250W; the spraying time of magnetron sputtering is 30min; after testing, the Cu content in the prepared Cu-Al-Ca bifunctional material is 0.81wt%, recorded as Cu-Al10-Ca90-0.81wt%.

[0093] Example 2

[0094] Cu-Al10-Ca90-1.7wt% was prepared by the same method as in Example 1, except that the magnetron sputtering time was changed to 60 min.

[0095] Example 3

[0096] Cu-Al10-Ca90-2.7wt% was prepared by the same method as in Example 1, except that the magnetron sputtering time was changed to 120 min.

[0097] Comparative Example 1

[0098] Commercially available CaO powder (brand: Aladdin, purity: 99.9%) was used as Comparative Example 1 and is denoted as CaO.

[0099] Comparative Example 2

[0100] The Al-Ca adsorbent particles (ie, Al10-Ca90) prepared in step S6 of Example 1 are used as Comparative Example 2 and are denoted as Al10-Ca90.

[0101] Performance Testing

[0102] Weigh the same mass of the above samples and put them into a fixed bed reactor. Heat the fixed bed reactor to 650°C and introduce flue gas with a CO2 concentration of about 15% into the reactor for CO2 capture. The CO2 is introduced for 30 minutes and then the ventilation is stopped. The cycle is repeated 10 times. The results are as follows: Figure 4 As shown in A.

[0103] The temperature of the fixed bed reactor was maintained at 650°C, and H2 was introduced into the fixed bed reactor to cause reverse water gas reaction. The concentration of hydrogen was 100%. The reaction was stopped after the H2 was introduced for 30 minutes. The cycle was repeated 10 times. The results are as follows: Figure 4 As shown in B and C.

[0104] As can be seen from the figure, the CO2 capture capacity, CO2 in-situ conversion rate and CO product selectivity of the Cu-Al-Ca bifunctional materials of Examples 1-3 are significantly better than those of Comparative Examples 1-2. Different Cu contents have a certain influence on the cyclic CO2 capture and in-situ conversion performance of the Cu-Al-Ca bifunctional materials. Among them, the Cu-Al10-Ca90-1.7wt.% bifunctional material still has a CO2 capture capacity of 13.3mmol / g, a CO2 conversion rate of 99% and a CO product selectivity of 100% after 10 cycles.

[0105] SEM / EDX-Mapping Test

[0106] The Cu-Al-Ca dual-functional material of the present invention was subjected to SEM / EDX-Mapping spectrum analysis, and the results are as follows: Figure 5 As shown in the figure, it can be seen that Al-Ca is evenly distributed and presents a fluffy porous structure, and Cu metal only covers the surface of the particles to form a coating layer.

[0107] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0108] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A Cu-Al-Ca dual-functional material with a core-shell structure, characterized in that: The core of the bifunctional material is an Al-Ca adsorbent composed of Al2O3 and CaO, and the shell is metal Cu; Wherein, based on the total mass of the Cu-Al-Ca dual-functional material, the mass fraction of metal Cu in the dual-functional material is 0.5-3.0wt%, Wherein, based on the total molar number of metal elements in the Cu-Al-Ca dual-functional material, the molar ratio of Al element to all metal elements is 1-10%.

2. A method for preparing the Cu-Al-Ca dual-functional material according to claim 1, characterized in that: The following steps are involved: S1: dissolving a Ca precursor and an Al precursor to obtain a metal ion solution; S2: dissolving citric acid in the metal ion solution to obtain a mixed solution; S3: stirring and heating the mixed solution to form a wet gel; S4: drying and aging the wet gel to form a dry gel; S5: calcining the dry gel to obtain Al-Ca adsorbent powder; S6: granulating the Al-Ca adsorbent powder to obtain Al-Ca adsorbent particles; S7: Spraying metal Cu on the Al-Ca adsorbent particles on a vibration table by magnetron sputtering to obtain the Cu-Al-Ca dual-functional material.

3. The preparation method according to claim 2, characterized in that: In step S1, The Ca precursor is calcium nitrate, the Al precursor is aluminum nitrate, the solvent used for dissolution is water, and the molar ratio of nitrate ions in the calcium nitrate and aluminum nitrate to water is 1:30 to 1:

50.

4. The preparation method according to claim 2 or 3, characterized in that: In step S2, The molar ratio of the metal ions to the citric acid in the metal ion solution is 1:1 to 1:1.

5.

5. The preparation method according to claim 2 or 3, characterized in that: In step S3, The stirring speed is 200-300 rpm, the heating is oil bath heating, and the temperature of the oil bath heating is 80-90°C.

6. The preparation method according to claim 2 or 3, characterized in that: In step S4, the drying and aging temperature is 110-140°C; In step S5, the calcination temperature is 750-900°C, and the calcination time is 1.5-4 hours.

7. The preparation method according to claim 2 or 3, characterized in that: In step S6, The granulation is performed using a hydraulic granulator, wherein the processing pressure is 10 MPa; The particle size of the Al-Ca adsorbent particles obtained after granulation is 40-60 meshes.

8. The preparation method according to claim 2 or 3, characterized in that: In step S7, In the magnetron sputtering, the Al-Ca adsorbent particles are placed on a vibration table, and the vibration frequency of the vibration table is 20-50 rpm; the spraying power of the magnetron sputtering is 200-250 W; and the spraying time of the magnetron sputtering is 30-120 min.

9. Use of the Cu-Al-Ca dual-functional material according to claim 1 for CO2 capture and in-situ reverse water gas shift to produce CO.

Citation Information

Patent Citations

  • Synthesis method and application of difunctional material for carbon dioxide capture and in-situ conversion

    CN119114083A